Application of organic-inorganic hybrid composite particle for removal of heavy metal ions from aqueous solution and its toxicity evaluation. (October 2017) - Lee, Soonjae; Kim, Nahae; Cho, Seulki; Ryu, Jae-Chun; Cho, Yoon; Park, Jeong-Ann; Lee, Sang-Hyup; Kim, Juyoung; Choi, Jae-Woo
Graphical abstract: Highlights: Amphiphilic polymer precursor is conjugated onto silica nanoparticles. The composite removed various heavy metal ions from aqueous solution. The composite is a promising adsorbent for hydrophilic and/or hydrophobic pollutants. Abstract: In this study, we present new organic–inorganic (O-I) hybrid composite particles and their possible application as an adsorbent for removal of various inorganic heavy metal from aqueous phase. The O-I hybrid nanoparticles were first prepared by copolymerization of (3-aminopropyl) triethoxysilane (APTES) and alkoxysilane-functionalized amphiphilic polymer (APAS) precursors which have hydrophobic polypropylene oxide segment and hydrophilic polyethylene oxide segment at the same backbones where triethoxysilane groups are chemically bonded with hydrophobic segment. The O-I hybrid composite particles consisting of silica nanoparticles chemically interconnected by O-I hybrid nanoparticles were prepared using the 2nd hydrolysis-condensation reaction. The characteristics of the hybrid particle thus developed were confirmed by FT-IR (Fourier transform infrared) spectroscopy, 29 Si-NMR (nuclear magnetic resonance) spectroscopy, EA (Elemental analysis), TGA (thermogravimetric analysis), SEM (scanning electron microscopy), and cryo-TEM (cryogenic transmission electron microscopy). The O-I hybrid particles exhibited removal of cations (Ni, Cu, Zn, Cd and Pb) from aqueous solution with a considerably higher sorption capacity for Pb than for other cations. The heavy metal removal occurred instantaneously with pH increase. A step wise application tests were conducted to distinguish between heavy metal precipitation at a high pH and adsorption by the developed material. Cytotoxicity tests demonstrated that the developed adsorbent has a weak cytotoxic effect on four different types of human cells.